2011
DOI: 10.1017/s000711451100033x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and reversal of diet-induced leptin resistance with a sugar-free diet despite high fat content

Abstract: Chronic consumption of a Western-type diet, containing both elevated sugar and fat, results in leptin resistance. We hypothesised that fructose, as part of the sugar component of Western-type diets, is one causative ingredient in the development of leptin resistance and that removal of this component will prevent leptin resistance despite high fat (HF) content. We fed rats a sugar-free (SF), 30 % HF (SF/HF) diet or a 40 % high-fructose (HFr), 30 % HF (HFr/HF) diet for 134 d. The HFr/HF diet resulted in impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 24 publications
1
69
0
1
Order By: Relevance
“…Our group has also shown that fructose (or sucrose) can exacerbate features of metabolic syndrome compared with pair-fed glucose-or starch-fed controls, even under settings of caloric restriction (9)(10)(11). Thus, whereas fructose intake may induce leptin resistance with impaired satiety and weight gain (12,13), fructose-induced metabolic syndrome may also occur, independent of increases in energy intake or weight gain.…”
mentioning
confidence: 72%
“…Our group has also shown that fructose (or sucrose) can exacerbate features of metabolic syndrome compared with pair-fed glucose-or starch-fed controls, even under settings of caloric restriction (9)(10)(11). Thus, whereas fructose intake may induce leptin resistance with impaired satiety and weight gain (12,13), fructose-induced metabolic syndrome may also occur, independent of increases in energy intake or weight gain.…”
mentioning
confidence: 72%
“…[109][110][111][112] The ability of fructose to cause obesity is not simply from its caloric value but rather from its capacity to induce leptin resistance (thereby blocking satiety responses) while at the same time reducing ATP production by blocking fat oxidation. 109,[113][114][115] Laboratory animals fed fructose develop features of metabolic syndrome and, if prone, will even develop diabetes. 116,117 Features of metabolic syndrome can be induced even with caloric restriction provided the sugar (or fructose) content is high, 116 demonstrating that it is not overnutrition but rather the presence of fructose that is responsible for the development of metabolic syndrome.…”
Section: The Rise In Intake Of Added Sugars and Their Effect On Africmentioning
confidence: 99%
“…These obese patients are hypothesized to develop leptin resistance that is commonly defined by the reduced capability of leptin to resist the development of obesity (Enriori et al, 2006;Morrison, 2008;Myers et al, 2008;Bjorbaek, 2009;Morris & Rui, 2009;Wong et al, 2013). Since the lack of response to leptin hinders cen- (Munzberg et al, 2005), and the type of diet (Shapiro et al, 2011), may also contribute to leptin resistance.…”
Section: Leptin Therapy and Leptin Resistancementioning
confidence: 99%